+0  
 
0
368
3
avatar+105 

-1^2

 Sep 16, 2018
 #1
avatar+4569 
+1

\(-1^2=-1*-1=\boxed{1}\).

smileysmiley

 Sep 16, 2018
 #2
avatar+2419 
+1

Hi, tertre!

 

\(-1^2=-1\).

 

This confuses most people, and this is a quite common error. I would like to correct it once and for all!

 

\(-1^2=-(1^2)=-(1*1)=-1\\ (-1)^2=-1*-1=1\)

 

Do you see the difference? The order of operations is strict.

TheXSquaredFactor  Sep 16, 2018
edited by TheXSquaredFactor  Sep 16, 2018
 #3
avatar+109519 
+1

Xsquared's  answer is the correct one.     laugh

You do need to bew careful though.

 

\(1)\;\;\;-1^2=-1*1^2=-1*1=-1\\~\\ 2)\;\;\;(-1)^2=-1*-1=+1=1\\~\\ 3)\;\;\; If \;\;x=-1\;\;then\;\; x^2=(-1)^2=+1\\~\\ 4)\;\;\; x^2=1\;\;find\;\;x \qquad \rightarrow \qquad x=\pm\sqrt1=\pm1\)

Melody  Sep 17, 2018

18 Online Users

avatar
avatar
avatar